2020
DOI: 10.3390/app10196984
|View full text |Cite
|
Sign up to set email alerts
|

Change of Direction Performance Is Influenced by Asymmetries in Jumping Ability and Hip and Trunk Strength in Elite Basketball Players

Abstract: Change of direction (COD) ability is essential for sport performance in high level team sports such as basketball, however, the influence of asymmetries on COD ability is relatively unknown. Forty-three junior and senior level elite basketball players performed isometric hip and trunk strength testing, passive hip and trunk range of motion testing, and unilateral horizontal and vertical jumps, as well as the T-test to measure COD performance. Mean asymmetry values ranged from 0.76% for functional leg length up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…While these studies collectively show that resistance exercise in gymnasts can improve jumping performance, speed, change of direction ability and sport-specific skills, our study was the fist to assess the effect of resistance exercise on single-joint strength. ILA of the hip peak torque that we observed was similar to that reported in a study conducted on male basketball players, 32 which could be attributable to shorter training history, as our sample was very young. Previous studies have assessed ILAs of isometric strength measurements of knee flexion and extension in athletes with varying age and skill level.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While these studies collectively show that resistance exercise in gymnasts can improve jumping performance, speed, change of direction ability and sport-specific skills, our study was the fist to assess the effect of resistance exercise on single-joint strength. ILA of the hip peak torque that we observed was similar to that reported in a study conducted on male basketball players, 32 which could be attributable to shorter training history, as our sample was very young. Previous studies have assessed ILAs of isometric strength measurements of knee flexion and extension in athletes with varying age and skill level.…”
Section: Discussionsupporting
confidence: 88%
“…31 Only one study, conducted on male basketball players, used a fixed dynamometer to assess PT of the hip muscles. 32 However, it cannot be easily compared to our study conducted on young female gymnasts. Of note, hip muscles and their imbalance or deficit have been identified as risk factors for lower limb (LL) injuries.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, we did not consider direction-specificity in this study. It has been implied that inter-limb asymmetries in lower limb strength are related to asymmetries in CoD performance [ 20 ]. However, it has been recently stressed that asymmetries in CoD ability should not be calculated based on raw test times.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the hip extensors, flexors, internal and external rotators, abductors and adductors, was assessed with the MuscleBoard dynamometer, in accordance with previous studies [ 19 , 20 ]. The dynamometer has been shown to provide highly reliable peak torque outcomes for the hip muscle groups [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Concerning motion asymmetries, two studies in this Special Issue examined potential relationships with performance. Ujakovič and Šarabon [3] reported asymmetries in jumping ability and hip and trunk strength to influence the change of direction performance in elite basketball players. Furthermore, as the magnitudes of asymmetry revealed to be highly dependent on the specific movement, test and parameter, the authors suggested not to use uniform asymmetry thresholds, such as <10%, when deciding on athletes' return to sport or when planning counteractive training interventions.…”
mentioning
confidence: 99%